Faktor-Faktor yang Berhubungan dengan Pemberian Asi Esklusif pada Anak Usia 7-12 Bulan di Puskesmas - Risma Eka Putri; Eka Afrika; Putu Lusita Nati Indriani (Bulletin of Community Engagement, 2024)
Providing proper nutrition in the first six months of a baby's life is by providing breast milk exclusively. Increasing the rate of breastfeeding mothers globally has the potential to save the lives of more than 820,000 children under five. Optimal breastfeeding can save the lives of more than 820,000 children under 5 years old every year. However, only around 36% of babies aged 0-6 months worldwide are exclusively breastfed. The aim of this research is to determine the relationship between knowledge, work and family support with the success of providing exclusive breastfeeding in the Abab Community Health Center Work Area in 2024. Type and Design of the Research is quantitative using an analytical survey method with a cross sectional approach. The research was carried out in June-July 2024 at the Abab Community Health Center with a population of all mothers with babies aged 7–12 months in the Abab Community Health Center working area of 95 people. The sample used was a total population of 95 respondents, using primary data obtained by filling in a questionnaire that had been prepared by the researcher and carrying out univariate and bivariate analysis using the che square test. The results of the univariate analysis of 95 respondents who did not exclusively breastfeed were 34 respondents (35.8%) and those who exclusively breastfed were 61 respondents (64.2%). The results of the chi-square statistical test showed that the mother's knowledge variable was found to be ρ value = 0.005, the mother's employment variable was ρ value = 0.028 and the family support variable was found to be ρ value = 0.023, which is smaller than α=0.05, indicating that there is a significant relationship between knowledge, work and support. families with exclusive breastfeeding in the Abab Community Health Center Working Area